Pengaruh Kepemilikan Keluarga, Karakteristik Dewan Komisaris, dan Kesibukan Komite Audit Terhadap Audit Report Lag: Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang terdaftar di Bursa Efek Indonesia tahun 2022-2024 - Nurul Wardhati; Erly Mulyani (Universitas Negeri Padang, 2026)
This study aims to analyze the effect of family ownership, board of commissioners’ characteristics, and audit committee busyness on audit report lag. The theoretical foundation of this research is based on agency theory and signaling theory. This research employs a causal study design with a quantitative approach. The sample was determined using a purposive sampling method, resulting in 92 companies from the consumer cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period, with a total of 276 observations. Data were analyzed using multiple linear regressions with the assistance of SPSS version 25. The finding indicate that family ownership, board size, and audit committee busyness have no significant effect on audit report lag. However, the proportion of independent commissioners, as one of the board characteristics, shows a significant influence on audit report lag.